Effect of Carrier Types and Spray Drying Temperature on the Physicochemical Properties of Turmeric tea - Norhelmi, Siti Aishah; Mohd Kassim, Angzzas Sari; Razali, Nor Faizah (Progress in Engineering Application and Technology, 2022)
Unhealthy beverages have a variety of negative health effects, yet people continue to drink them because they taste good so this triggered the need for a better, healthier and instant beverages as alternatives, and the quality of the resulting powder is determined by the operational variables and parameters in the spray drying process. The low glass transition temperature of the low molecular weight sugars included in such goods, primarily sucrose, glucose, and fructose, causes powder stickiness. The study was conducted to extract bioactive compound of turmeric using subcritical water extraction and formulate basis for tasty turmeric tea, to determine suitable inlet air temperature of spray dryer to produce turmeric tea granules based on the best physicochemical properties, to determine the best type of carrier agent and its concentration to produce turmeric tea granules based on the best physicochemical properties and to evaluate the total phenolic content and total antioxidants activity of the produced turmeric tea granules. The bioactive ingredients of turmeric were extracted using subcritical water extraction. The tea granules were obtained using spray drying process with the inlet temperature of 190, 200 and 210 oC. The best inlet temperature and type of carrier (Arabic gum vs. maltodextrin) were determined via optimization of yield, moisture content and solubility. The physicochemical analysis, TPC and TAA were also quantified. The study successfully determined the best inlet temperature at 190 oC and 6% maltodextrin as the optimum carrier for highest yield (0.27 g/100g) and solubility (88.50 %). The TPC of turmeric tea increased due to heat treatment from spray drying. Meanwhile, the TAA of turmeric tea decreased 56.578 % after spray drying process but the TAA increased to 77.177 % when Arabic gum was used as the carrier. The findings of this study will shed the understanding upon the production of an alternative instant tea that is healthier and with better nutritional contents.